(untitled) (Global Journal of Human-Social Science, 2024)
The focus of this study is the use of Smart Contracts in the administration of legal documents with the aim of examining the level of legal certainty resulting from their implementation How could smart contracts bring legal certainty to an agreement between parties Possible obstacles to the widespread adoption of smart contracts such as the limited accessibility of the technology to society in general will be recognized Finally it aims to elucidate how smart contracts can bring legal certainty to the parties involved and examines their relevance in contemporary society Although the advantages they bring are recognized there is a valid concern about the possible exclusivity of access to this technology thus restricting its availability to more knowledgeable individuals with greater resources